Sub-surface identification of iron sand in Lamreh, Aceh Besar using very low frequency method. Issue 1 (February 2021) - Jannah, M; Muhammad; Marwan; Jalil, Zulkarnain
Abstract: This work was studied about 2D Sub-Surface Identification of iron sands in Lamreh, Aceh Besar by using Very Low Frequency method based on Resistivity mode (VLF-R). The aims of the research; (1) Predicting 2D sub-surface of iron sands resistivity in Lamreh based on VLF data. (2) Conducting 2D sub-surface identification measurement data of iron sands. VLF data were measured into 3 lines, by the first line was 250 meters and the second line was 120 meters and the third lines was 100 meters. 2D modelling in VLF-R was conducted by using 2LAYINV electromagnetic inversion program. Inversion process showed 2-iron sands-conductivity-zone, where the resistive layer in depth was covered by conductive layer on it. The conductive layer was expected as clay being rich of water content by resistivity rate at 10 – 100 Ωm. Resistive layer was expected as cap rock by resistivity rate at 20000 – 40000 Ωm.